Research methods and society : foundations of social inquiry - Dorsten, Linda Eberst; Hotchkiss, Lawrence (New York Routledge, 2019)
Research Methods and Society, Third Edition is designed to help undergraduate students acquire basic skills in methods of social science research. These skills provide a foundation for understanding research findings in the social sciences and for conducting social research. Just as important, such skill-sets and principles can be applied to everyday situations to make sense of the endless stream of claims and counterclaims confronted daily in print and electronic forms, including social media.
Keywords: Social sciences-Research-Methodology; Sociology-Research-Methodology